System of playful activities to improve writing skills in the english language - Ullauri Aguilar, Katherine Lisseth; Orellana Román, Kerly Mishel (Machala: Universidad Técnica de Machala, 2025)
The present research project aimed to design and implement a system of workshops with playful activities to improve writing skills in English among tenth-grade students of Basic General Education in an educational institution in the city of Machala. The identified issue was the students’ low performance in written English, attributed to traditional teaching methods, lack of motivation, and limited meaningful language practice. The proposal was grounded in the theoretical contributions of Dewey (1938), who advocated for experiential learning; Ausubel (1983), with this theory of meaningful learning; and Hymes (1971), who emphasized communicative competence as a core element in language instruction. The research followed a quantitative approach with a pre-experimental design, involving a sample of 32 students. Theoretical methods (historical-logical, analytic-synthetic, systemic, and hypothetical-deductive) and empirical methods (observation and surveys) were used. The implemented system integrated playful activities targeting the linguistic, cognitive and pragmatic dimensions of writing, including language games, group dynamics, creative writing, and visual prompts. The results showed a significant improvement in students’ writing performance, particularly in linguistic and pragmatic aspects. However, the cognitive dimension showed more modest progress, highlighting the need to reinforce strategies that promote idea organization and critical thinking in future applications. It is concluded that playful workshops foster motivation, participation, and meaningful learning, offering an effective and replicable teaching alternative in similar educational contexts.
El presente trabajo de investigación tuvo como objetivo diseñar e implementar un sistema de talleres con actividades lúdicas para mejorar la habilidad de escritura en el idioma inglés en estudiantes de décimo año de Educación General Básica en una institución educativa de la ciudad de Machala. La problemática detectada fue el bajo nivel de desempeño escrito en inglés, debido al uso de metodologías tradicionales, escasa motivación y limitada práctica significativa del idioma. La propuesta se fundamentó en los aportes de Dewey (1938), quien promovió el aprendizaje activo y experiencial; Ausubel (1983), con su teoría del aprendizaje significativo; y Hymes (1971), al considerar la competencia comunicativa como elemento esencial en la enseñanza de lenguas. La investigación se enmarcó en el enfoque cuantitativo, con un diseño pre-experimental aplicado a una muestra de 32 estudiantes. Se utilizaron métodos teóricos (histórico-lógico, analítico-sintético,sistémico e hipotético-deductivo) y empíricos (observación y encuestas). El sistema implementado integró actividades lúdicas orientadas a las dimensiones lingüística, cognitiva y pragmática de la escritura, incluyendo juegos lingüísticos, dinámicas grupales, escritura creativa y recursos visuales. Los resultados evidenciaron una mejora significativa en la competencia escrita, especialmente en los aspectos lingüísticos y pragmáticos. No obstante, la dimensión cognitiva mostró avances más discretos, por lo que se recomienda profundizar en estrategias que estimulen la organización de ideas y el pensamiento crítico en futuras implementaciones. Se concluye que los talleres lúdicos fomentan la motivación, participación y aprendizaje significativo, representando una alternativa didáctica eficaz y replicable en otros contextos similares.
Keywords: WRITTEN SKILLS; ENGLISH LANGUAGE; PLAY ACTIVITIES; WORKSHOP SYSTEM; TEACHING-LEARNING; GAMIFICATION